PENINGKATAN KUALITAS PRODUK CRUMB RUBBER DENGAN MENGGUNAKAN METODE QUALITY FUNCTION DEPLOYMENT - Laulia Ariyani Rangkuti; A. Jabar M. Rambe; Rosnani Ginting (Jurnal Teknik Industri USU, 2014)
Quality of the product is important factor to determine success of a company. The product will be qualified if the company meet the customer’s need and desire. Product crumb rubber type SIR 20 has low quality because there are products over limit from tolerancy standar based plasticity retention index test and dirt content test. Standart PRI and dirt content based Standar Nasional Indonesia (SNI) is minimum 50%, and maksimum 0,2%. The average of actual quality test for product crumb rubber type SIR 20 based plasticity retention index test and dirt content test is 59,46% and 0,22%. The result of the product quality test show the company has not to fill standar quality of the product. The product has low quality can make production cost increase. The proper technique to solve this problem is Quality Function Deployment (QFD). Based on the results of the approach taken by the QFD obtained 15 variables consumer needs and 6 technical characteristics of the Crumb Rubber Type SIR 20 product which is the variable "production cost" is the first priority in improvement quality with the value of the highest interest rate that is 21%.